Scientific research in biomedical studies: insights and barriers at the University of Sarajevo - Nejra Selak; Meliha Šehić; Bakir Kudić; Ismar Ećo; Behija Spahić Šehić; Aida Kulo Ćesić (Medicinski glasnik, 2025)
Aim: The position of science and scientific research in Bosnia and Herzegovina (B&H) is unfavourable. University education lacks research programs, hindering students from developing critical evaluation skills. Methods: This cross-sectional study examined knowledge, attitudes, experience and perceived barriers towards scientific research among biomedical students and recent graduates at the University of Sarajevo in B&H. A self-reporting questionnaire was distributed via social networks and among students from all years of the Medical, Dentistry, Pharmaceutical faculties, the Faculty of Health Sciences, and the Faculty of Science, as well as recent graduates. Results: The survey was completed by 243 participants. The mean knowledge score of 4.3/11 was noticed; 216 (96%) believed research was necessary for healthcare improvement. Although 147 participants (65.3%) attended courses on research methodology, only 63 (28%) engaged in scientific research at their faculties. Only 5 (8.5%) employed graduates participated in research at their jobs. Almost half, 99 (44%) participants consulted scientific papers only upon recommendation. The majority of participants, 199 (82.2%), reported they experienced barriers to conducting research in B&H. Conclusion: Biomedical students and graduates demonstrated limited research knowledge, but had positive attitudes and acknowledged significant barriers. Improved faculty curricula in research areas and more opportunities are needed.
Keywords: Biomedical research; Bosnia and Herzegovina; curriculum; students